Review of methods for assessing the cost-effectiveness of medical interventions - T. I. Busheva; A. A. Kurylev (Реальная клиническая практика: данные и доказательства)
Assessment of the effectiveness of a drug is a complex process. Currently, the standard method for assessing the effectiveness of a medical intervention is the quality-adjusted life years (QALY). In the summer of 2024, a description of a new method for assessing the effectiveness of medical interventions — Standard of Living Valuation (SoLV) was published. The proposed method is more difficult than QALY, but its capabilities are broader. However, this method is also not optimal. The problem of creating an optimal method for assessing the cost-effectiveness of health technologies remains open.